EFFICACY OF FUNGICIDES-XLVI: EFFECT OF FUNGICIDAL SEED TREATMENT AGAINST HEAVY INOCULUM PRESSUREOF CERTAIN FUNGI CAUSING DISCOLOURATION OF PADDY SEEDS - DHARAM VIR, A. K. MISRA* AND (Indian Phytopathology, 2002)
The fungi causing discolouration of paddy seeds were observed to cause deleterious effect on seed germination under heavy inoculum pressure. The effect was most pronounced with Pyricularia oryzae and Fusarium equiseti. Fungicidal seed treatment provided protection against these fungi resulting in distinct improvement in germination.